Investigation of the effect of titanium and zirconium oxides on the strength characteristics of nanoscale hydroxyapatite - K.I. Sabanin; V.M. Skachkov; I.S. Medyankina; E.A. Bogdanova; N.A. Sabirzyanov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The article discusses the possibility of dispersion strengthening of nanostructured hydroxyapatite synthesized by precipitation from solution introducing reinforcing additives of non-stoichiometric titanium oxide and zirconium dioxide. The reinforced composite material: hydroxyapatite – non-stoichiometric titanium oxide – zirconium dioxide was obtained by mechanochemical synthesis of hydroxyapatite with doping components followed by annealing at 1000°C. The initial components and synthesized samples were certified using modern physicochemical methods of analysis: X-ray phase analysis, differential thermal analysis, scanning electron microscopy, surface area and porosity analysis, dispersion analysis. The influence of the qualitative and quantitative composition of the composite on the sintering processes and strength characteristics of the studied samples in a wide temperature range of 25-1200°C is shown. It has been experimentally established that the most promising system for developing biocomposites based on it ishydroxyapatite – 15% non-stoichiometric titanium oxide – 5% zirconium dioxide. Composite materials of this composition have a dense, uniform, strong structure with a high degree of crystallinity and a developed surface. They seem to be promising materials for further research with the aim of introducing it into medical practice.